Pengembangan Media Pembelajaran Geografi Pada Materi Sistem Informasi Geografis (SIG) Untuk Meningkatkan Hasil Belajar Siswa Kelas X SMA Negeri 6 Kota Gorontalo Menggunakan Edpuzzle - Dumako, Nadhila Oktarisa; Eraku, Sunarty Suly; Pambudi, Moch Rio (Universitas Negeri Gorontalo, 2025)
The use of technology is increasingly on the rise, and the importance of information technology is also manifested in various aspects of life, such as in communication, access to information, and also in the learning process.Interactive learning platforms can be effective teaching tools to enhance student understanding and retention, one of which is Edpuzzle.The purpose of this research is to develop geography learning media using Edpuzzle on the topic of geographic information systems (GIS).Analyzing the feasibility of the media as a geography learning tool.This research is a development and research study, also known as Research and Development (RD).The development model used is the ADDIE development model, which has 5 stages including analysis, planning, development, implementation, and evaluation.In the first stage or development stage, the learning media using eddpuzzle was evaluated by several validators and 30 students from class X at SMA Negeri 6 Gorontalo City.The assessment results by subject matter experts were 85.71% (very feasible), the media expert assessment was 82.67% (very feasible), while the geography teacher's assessment reached 90% (very feasible) and the student assessment obtained 87.33% (very feasible).Based on the assessment results from the validators and students, it can be concluded that the Development of Geography Learning Media on Geographic Information System (GIS) Material to Improve the Learning Outcomes of Class X Students at SMA Negeri 6 Gorontalo CityUsing Edpuzzle is already suitable for use in learning.